Comprehensive, blinded assessment of balance in orthostatic tremor. (February 2018) - Bhatti, Danish; Thompson, Rebecca; Xia, Yiwen; Hellman, Amy; Schmaderer, Lorene; Suing, Katie; McKune, Jennifer; Penke, Cynthia; Iske, Regan; Roeder, Bobbi Jo; Siu, Ka-Chun; Bertoni, John M.; et al.
Abstract: Introduction: Orthostatic Tremor (OT) is a movement disorder characterized by a sensation of unsteadiness and tremors in the 13–18 Hz range present upon standing. The pathophysiology of OT is not well understood but there is a relationship between the sensation of instability and leg tremors. Despite the sensation of unsteadiness, OT patients do not fall often and balance in OT has not been formally assessed. We present a prospective blinded study comparing balance assessment in patients with OT versus healthy controls. Methods: We prospectively enrolled 34 surface Electromyography (EMG)-confirmed primary OT subjects and 21 healthy controls. Participants underwent evaluations of balance by blinded physical therapists (PT) with standardized, validated, commonly used balance scales and tasks. Results: OT subjects were mostly female (30/34, 88%) and controls were majority males (13/20, 65%). The average age of OT subjects was 68.5 years (range 54–87) and for controls was 69.4 (range 32–86). The average duration of OT symptoms was 18 years. OT subjects did significantly worse on all the balance scales and on most balance tasks including Berg Balance Scale, Functional Gait Assessment, Dynamic Gait Index, Unipedal Stance Test, Functional Reach Test and pull test. Gait speed and five times sit to stand were normal in OT. Conclusions: Common validated balance scales are significantly abnormal in primary OT. Despite the objective finding of impaired balance, OT patients do not commonly have falls. The reported sensation of unsteadiness in this patient population seems to be out of proportion to the number of actual falls. Further studies are needed to determine which components of commonly used balance scales are affected by a sensation of unsteadiness and fear of falling. Highlights: Orthostatic tremor subjects have abnormal results on commonly used balance scales including the Berg Balance Scale. The abnormal balance scale results could be due to either true imbalance or to fear of falling. Orthostatic tremor subjects have normal gait speed.